Polluted Waters Use in the Urban Agriculture and Its Impact on the Quality of the Grown Vegetables - Ilunga Mpanga, Fabien; Shengo Lutandula, Michel (The Global Environmental Engineers, 2020)
Urban agriculture has become a common practice in major urban agglomerations, particularly in the mining region of Katanga, in the Democratic Republic of Congo (DRC). However, this agriculture is based on the production of vegetables grown on the soil contaminated by industrial water and domestic wastewater, wherein one finds heavy metals and pathogenic microbes capable of endangering the consumer’s health. This work has been carried out in view of contributing to the consumer’s health protection and endeavours at establishing, based on physicochemical and mineral analyses of water samples, the soil used in the urban agriculture and edible plants, a link between the use of contaminated waters in the urban agriculture, the build-up of heavy metals in the soil and the possible contamination by heavy metals of vegetables grown (amaranths and broccolis) in the Kasungami district and consumed by the population living in the City of Lubumbashi (DRC). The results given by the analyses of water, soils and vegetable samples revealed that, apart from cobalt, other heavy metals were present in water used in the urban agriculture to concentrations below quality standards. As for the soil, it contained heavy metals to concentration reputed phytotoxic. However, only the broccolis were contaminated with lead, contrarily to amaranths in which heavy metals were present to concentrations below quality standards. These findings enabled concluding that urban agriculture of vegetables encountered in the large agglomerations of the DRC could endanger the consumers’ health and measures need to be taken in view of preventing heavy metal from entering the food chain.